Dynamic right ventricular and atrial volume responses to exercise in endurance-trained and untrained healthy individuals - Björn Östenson; Ellen Ostenfeld; Jonathan Edlund; Håkan Arheden; Katarina Steding-Ehrenborg (PLoS ONE, 2026)
Aims Left ventricular (LV) function is enhanced during exercise in endurance-trained (ET) compared to untrained (UT) healthy individuals. However, the volume responses of the right ventricle (RV), left atrium (LA), and right atrium (RA) during exercise have not been studied in the same subject simultaneously and while standardizing for the respiratory influence on cardiac volumes. The aim was therefore to investigate how the four-chambered heart responds to exercise in ET and UT healthy individuals using exercise real-time cardiac magnetic resonance imaging (CMR) while controlling for effects of respiration. Materials and methods Twenty ET (9 women) and 13 UT healthy individuals matched for age and sex underwent CMR at rest and during moderate and vigorous exercise. LV and RV end-diastolic and end-systolic volumes (EDV and ESV), stroke volumes (SV) and maximal and minimal LA and RA volumes (LAV max , RAV max and LAV min , RAV min ) were measured at end expiration. Results LVEDV and LVESV decreased during exercise in both groups. RVEDV and RVESV decreased during exercise in ET but was unchanged in UT. LAV max and LAV min were unchanged from rest to vigorous exercise in both groups. RAV max decreased during exercise in ET whilst RAV min was unchanged, and RAV max and RAV min were unchanged in UT. Thus, the RV and RA volume responses during exercise differed between ET and UT. Conclusion This study shows differences between ET and UT healthy individuals in adaptations to exercise when examining the four chambers simultaneously and even when standardizing for respiratory influences. This contributes to increased understanding of the RV volume adaptations in ET.